Green infrastructure in relation to informal urban settlements - Adegun, Olumuyiwa Bayode (Journal of Architecture and Urbanism, 2017)
Green infrastructure plays a critical role in environmentally sustainable urbanization in developing countries. Based on a review of academic outputs, this paper explores green infrastructure in the context of informal urban settlements. It identifies three ways informal settlements are connected to green spaces and natural ecosystems functioning as urban green infrastructure and then shows examples of benefits derived (ecosystem services) by the urban poor from these connections. Undesirable aspects and negative outcomes, regarded as ecosystem disservices, from the connection to natural ecosystems are also pointed out. The potentials of enhancing ecosystem services in terms of improving quality of life and the environment in informal settlements came to the fore. This work contributes to the growing body of knowledge on urban green infrastructure from the perspective of informal settlements in developing countries.